Atribusi Bawahan terhadap Pemimpin Berkarisma - Thalib, Darmawan; Fitriana, Dita; Anou, Enias; Maisyaroh, Maisyaroh; Sumarsono, Raden Bambang (Tarbawi, 2019)
This study aimed to see how the effectiveness of charismatic leadership when viewed from the perspective of a subordinate that examined from previous research articles. In this study, researcher also used a qualitative approach with the type of research is study of literature. The data collection technique is done by collecting both primary and secondary literature which is analyzed and presented. The results obtained indicate that in a subordinate's perception of charismatic leadership can be influenced by physical and psychological aspects. The physical aspect shows that leadership can be perceived as charismatic when viewed from gender and age. While the psychological aspect shows leadership can be perceived as charismatic if it is able to create a sense of trust, satisfaction, and feelings of empowerment from subordinates.